2016
DOI: 10.3390/molecules21101396
|View full text |Cite
|
Sign up to set email alerts
|

20(S)-Protopanaxadiol Phospholipid Complex: Process Optimization, Characterization, In Vitro Dissolution and Molecular Docking Studies

Abstract: 20(S)-Protopanaxadiol (PPD), a bioactive compound extracted from ginseng, possesses cardioprotective, neuroprotective, anti-inflammatory, antiestrogenic, anticancer and anxiolytic effects. However, the clinical application of PPD is limited by its weak aqueous solubility. In this study, we optimized an efficient method of preparing its phospholipid complex (PPD-PLC) using a central composite design and response surface analysis. The prepared PPD-PLC was characterized by differential scanning calorimetric, powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 61 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…26 The phospholipid-active ingredient is responsible for the creation of a hydrogen connection between the polar head and the active ingredient's polar functionalities. 25,27 In summary, as presented in Figure 2, the hydroxyl groups of polyphenols can interact effectively with nitrate and phosphate groups of phospholipids.…”
Section: Phytosome Structure and Preparation Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…26 The phospholipid-active ingredient is responsible for the creation of a hydrogen connection between the polar head and the active ingredient's polar functionalities. 25,27 In summary, as presented in Figure 2, the hydroxyl groups of polyphenols can interact effectively with nitrate and phosphate groups of phospholipids.…”
Section: Phytosome Structure and Preparation Methodsmentioning
confidence: 93%
“…Many authors have stated that the hydrogen interactions are the main interactions in phytosome vesicles. 25 Phospholipids have an affinity for polyphenols and form supramolecular adducts that have a definite stoichiometry, which can be obtained from thermal analysis. Semalty et al tested this parameter and found that hydrogen bond formation or hydrophobic interactions were due to the interaction between the two molecules.…”
Section: Phytosome Structure and Preparation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sample was placed on aluminum pans, and heated at a rate of 40 °C/min under an argon atmosphere was used from 40 to 600 °C. 18 Using Cu (1.54060 A) as a source of radiation, the P-XRD spectra for the same samples were recorded on a Shimadzu XRD 6000 diffractometer. The data was taken at a step size of 0.02 degrees and a time per step of 0.15 seconds throughout an angular range of 5 to 80 degrees.…”
Section: Predicted Intermolecular Hydrogen Bond Search With Data Anal...mentioning
confidence: 99%
“…10) Additionally, the favorable biocompatibility of phospholipid (PC) allows it to penetrate the cell membranes easily, and studies have reported that PC is capable of enhancing the solubility of drugs due to their amphiphilic nature, thereby improving their permeation and oral absorption. 11,12) For another, hydroxypropyl-β-cyclodextrin (HPCD) has already been confirmed as an excellent enhancer of drug solubility. 13) Meanwhile, the carrier formed by combinations of different carriers may exhibit the advantages of each single carrier, which have a synergistic effect on drug delivery.…”
Section: Introductionmentioning
confidence: 99%